THE IMPLEMENTATION OF ONLINE FEATURES OF BLENDED LEARNING METHOD IN CRITICAL READING CLASS AT B UNIVERSITY - Samuel Timotius Suhenri; Herwindy Maria Tedjaatmadja (Kata Kita: Journal of Language, Literature, and Teaching, 2016)
This thesis is a study of the online aspects of Blended Learning Method implementation and the example implemented in the Critical Reading class in B University. The purposes of the study are to see the implementation of the online aspects of the blended learning criteria in the classroom and the example of its implementation. The theory used is the criteria of blended learning class from Thorne (2003). The finding revealed that most of the criteria are implemented. However, the findings only focused on online features, so there will be some points not implemented in the class, since it could be implemented in offline class. Some examples of the implementation were the usage of Moodle as a help to adapt to blended learning method, usage of wide range of option in giving task and assignments to students, and giving access to contact the most appropriate person in the class.